Economics of literary translation: A simple theory and evidence - Victor Ginsburgh; Shlomo Weber; Sheila Weyers (Fondazione Eni Enrico Mattei (FEEM), 2008)
Books are an important factor of cultural transmission, but need, in most cases, to be translated. According to some authors, this may lead to a form of cultural domination of English. The population speaking English as a first language is, with the exception of Mandarin, the largest in the world. It is therefore not surprising that English produces more fiction (and much more scientific literature, as scientists from all countries write in English with increasing frequency) than any other language. We develop a theoretical model of translation, which is estimated on the basis of UNESCO translation data. We show that translations from English are dominated by translations from other languages, including Scandinavian ones and French.
Keywords: L82; Z11; 330; Languages; Translations; Cultural and Linguistic Distances; Sprache; Englisch (Sprache); Übersetzung; Wettbewerb; Theorie